2020
DOI: 10.1002/jgh3.12330
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric inflammatory bowel disease: Is it really uncommon in Asian children?

Abstract: Background/Aim: Inflammatory bowel disease (IBD) is said to be rare in Asian children, and there is scarce information from India. We therefore analyzed our experience of pediatric IBD. Methods: Prospectively maintained data of 105 consecutive children [median age 12 (IQR:7-14) years, 71 males] with IBD from July 2001 through June 2016 were retrospectively analyzed. Their detailed clinical features, endoscopic appearance, histopathology, and treatment outcomes were recorded. For Crohn's disease (CD), disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…13,14,20 There are other studies that reported male predominance in the Asian pediatric CD population, whereas no difference in the prevalence between males and females was seen in the EUROKIDS study. 23,25,26 Hong et al 13 explained the male predominance being due to the skewed sex ratio of the province during the enrolment period; our study overcomes this limitation and is more representative of the prevalence since it is a nationwide multicenter study. The male predominance in pediatric CD in the Asia-Pacific region might be due to ethnicity or environmental influences, since these regions share similar environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…13,14,20 There are other studies that reported male predominance in the Asian pediatric CD population, whereas no difference in the prevalence between males and females was seen in the EUROKIDS study. 23,25,26 Hong et al 13 explained the male predominance being due to the skewed sex ratio of the province during the enrolment period; our study overcomes this limitation and is more representative of the prevalence since it is a nationwide multicenter study. The male predominance in pediatric CD in the Asia-Pacific region might be due to ethnicity or environmental influences, since these regions share similar environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 89%
“…The male predominance in pediatric CD in the Asia-Pacific region might be due to ethnicity or environmental influences, since these regions share similar environmental and genetic factors. [25][26][27] The mean age at diagnosis was 14.4 years for both CD and UC patients. A previous study reported a younger age at diagnosis of IBD in Korea, being 12.0 years for CD and 12.6 years for UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CD was patchy as Indian data were scarce, with only a few available reports 1,2 A preliminary study 3 showed that IBD comprises 0.03% of the outpatient case workload in South India and subsequent studies which followed suit showed that the incidence of IBD and its variability of the caseload in various parts of the country. [4][5][6] Global data show a wide distribution of 3-4/100,000 individuals every year, with variation in North America, Europe, and the rest of the world. 7 There seems to be male preponderance (1.5:1).…”
Section: Epidemiologymentioning
confidence: 99%
“…There is a surge in the pediatric inflammatory bowel disease (PIBD) cases diagnosed in the last decade. (1) Srivastava et al in a multicentric study from India have shown Crohns disease(CD) as the most common type, occurring in two thirds of the overall PIBD patients. It is well known that adolescents form a large proportion of the PIBD, with >50% of the cases occurring in the 10-18years age group (2) Imaging of the bowel is required as a part of small bowel evaluation at diagnosis in all IBD patients except typical ulcerative colitis(UC).…”
Section: Introductionmentioning
confidence: 99%